Sustained compression and healing of chronic venous ulcers. Issue 6657 (5th November 1988) - Blair, S. D.; Wright, D. D.; Backhouse, C. M.; Riddle, E.; McCollum, C. N.
Abstract : STUDY OBJECTIVE--Comparison of four layer bandage system with traditional adhesive plaster bandaging in terms of (a) compression achieved and (b) healing of venous ulcers. DESIGN--Part of larger randomised trial of five different dressings. SETTING--Outpatient venous ulcer clinic in university hospital. PATIENTS--(a) Pressure exerted by both bandage systems was measured in the same 20 patients. (b) Healing with the four layer bandage was assessed in 148 legs in 126 consecutive patients (mean age 71 (SE 2); range 30-96) with chronic venous ulcers that had resisted treatment with traditional bandaging for a mean of 27.2 (SE 8) months. INTERVENTIONS--(a) Four layer bandage system or traditional adhesive plaster bandaging for pressure studies; (b) four layer bandaging applied weekly for studies of healing. END POINTS--(a) Comparison of pressures achieved at the ankle for up to one week; (b) complete healing within 12 weeks. MEASUREMENTS AND MAIN RESULTS--(a) Four layer bandage produced higher initial pressures at the ankle of 42.5 (SE 1) mm Hg compared with 29.8 (1.8) for the adhesive plaster (p less than 0.001; 95% confidence interval 18.5 to 6.9). Pressure was maintained for one week with the four layer bandage but fell to 10.4 (3.5) mm Hg at 24 hours with adhesive plaster bandaging. (b) After weekly bandaging with the four layer bandage 110 of 48 venous ulcers had healed completely within 12 (mean 6.3 (0.4)) weeks. CONCLUSION--Sustained compression of over 40 mm Hg achieved with a multilayer bandage results in rapid healing of chronic venous ulcers that have failed to heal in many months of compression at lower pressures with more conventional bandages.